Understanding bandwidth constraints on South African university students during the COVID-19 pandemic - Lakay, Mc Guigan (Department of Computer Science, 2026)
Remote online teaching and learning have been used for many years by various institutions to add to the university experience and enhance the availability of educational content to students. However, there is a section of the student population that has not been able to take advantage of this enhancement. This includes those who come from under-privileged backgrounds or who live in underprivileged areas with a lack of resources. Research has found that this problem worsened due to the Covid-19 pandemic and lockdown. Many higher education institutions around the world proceeded to migrate their courses online, which left lower-income, low-resourced students with many challenges. Some institutions recognized some of these challenges and provided students with assistance to mitigate the impact of these challenges. For example, some students faced bandwidth constraints that limited their capabilities to participate in online courses. Some institutions provided internet data bundles as a measure to mitigate this issue. This study investigates the impact that the Covid-19 lockdown had on students at South African universities during the migration to online courses while experiencing bandwidth and access challenges. The methods used by the universities to assist students to mitigate these challenges have been explored as well. This investigation aims to raise awareness about the potential exclusion of students and the bandwidth and access constraints faced. Students completed a questionnaire regarding their online learning experience during the Covid-19 lockdown and the challenges related to their device and internet access. This was done to understand the bandwidth constraints for students during their studies. Secondly, the researcher interviewed students who were participating in online learning during the Covid-19 lockdown to gain insight into the challenges experienced. Finally, students installed a mobile application that monitored their data usage on certain applications for two months. The three data sources were analyzed together using descriptive and thematic analysis to answer the research questions. This study included student participants from two universities within the Western Cape, South Africa. An invitation to participate in this study was sent to all students at these institutions, however, only 266 responded. The final count of participation was that 92 validated participants completed the questionnaire; 10 students were interviewed, and 13 students participated in the mobile application field study. Page 2 of 2 The results suggest the shift to remote learning has worsened certain students' access to a capable device and reliable internet. The experiences using the online learning platforms were dependent on the student's device and internet access. Internet constraints led to students being excluded from some parts of classes or even the entire class. Lastly, the intervention of university-provided data bundles was significantly used, and many students relied on it to complete their courses. The zero-rated services were not utilized, and the data suggested that the services offered by universities should be better communicated. This study provided detailed data on the challenges that can be used to create awareness of the students that are being negatively affected and the assistance that they need. Future work suggests gaining data from a broader audience by reaching out to more devices, students, and universities.